Ad Hoc Networks First International Conference, ADHOCNETS 2009, Niagara Falls, Ontario, Canada, September 22-25, 2009. Revised Selected Papers - Zheng, Jun.; Mao, Shiwen; Midkiff, Scott F.; Zhu, Hua.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the refereed proceedings of the First International Conference on Ad Hoc Networks, held in Niagara Falls, Ontario, Canada, in September 2009. The 62 revised full papers presented were carefully reviewed. Ad hoc networks refer to the wireless networking paradigm that covers a variety of network forms for specific purposes, such as mobile ad hoc networks, sensor networks, vehicular networks, underwater networks, underground networks, personal area networks, and home networks. The various forms of ad hoc networks promise a broad scope of applications in civilian, commercial, and military areas, which have led to significant new research problems and challenges, and have attracted great efforts from academia, industry, and government. This unique networking paradigm necessitates re-examination of many established wireless networking concepts and protocols, and calls for developing new fundamental understanding of problems such as interference, mobility, connectivity, capacity, and security, among others. While it is essential to advance theoretical research on fundamentals and practical research on efficient algorithms and protocols, it is also critical to develop useful applications, experimental prototypes, and real-world deployments to achieve a practical impact on our society for the success of this networking paradigm.
1st ICST International Conference on Ad Hoc Networks -- Supporting Proactive Application Event Notification to Improve Sensor Network Performance -- An Energy-Efficient Cluster-Head Selection Protocol for Energy-Constrained Wireless Sensor Networks -- Optimization of Cluster Heads for Energy Efficiency in Large-Scale Wireless Sensor Networks -- Optimal Cluster Sizes for Wireless Sensor Networks: An Experimental Analysis -- A Parallel Paths Communication Technique for Energy Efficient Wireless Sensor Networks -- Scalable Max-Min Fairness in Wireless Ad Hoc Networks -- Upper Bounding Service Capacity in Multihop Wireless SSMA-Based Ad Hoc Networks -- QoS over Real-Time Wireless Multi-hop Protocol -- Efficient Distribution of Large Files in UMTS Supported by Network Coded M2M Data Transfer with Multiple Generations -- Enhancement of Self-organisation in Wireless Networking through a Cross-Layer Approach -- SPECS: Secure and Privacy Enhancing Communications Schemes for VANETs -- Security and Privacy in a Sensor-Based Search and Rescue System -- Computationally Efficient Mutual Entity Authentication in Wireless Sensor Networks -- Distributed Detection of Wormhole Attacks in Wireless Sensor Networks -- Power-Aware Intrusion Detection in Mobile Ad Hoc Networks -- DHT-Based Detection of Node Clone in Wireless Sensor Networks -- Connectivity-Aware Minimum-Delay Geographic Routing with Vehicle Tracking in VANETs -- Buckshot Routing - A Robust Source Routing Protocol for Dense Ad-Hoc Networks -- Enhanced Route-Split Routing Tolerant to Multiple Concurrent Link Failure for Mobile Ad Hoc Networks -- A Simulation-Based Performance Analysis of Various Multipath Routing Techniques in ZigBee Sensor Networks -- Centralized Routing and Scheduling Using Multi-Channel System Single Transceiver in 802.16d -- Contact Time in Random Walk and Random Waypoint: Dichotomy in Tail Distribution -- Throughput Analysis of IEEE 802.11 DCF in the Presence of Transmission Errors -- Effects of Unintentional Denial of Service (DOS) Due to Push-to-Talk (PTT) Delays on Performance of CSMA/CA Based Adhoc Land Mobile Radio (LMR) Networks -- Achievable Region in Slotted ALOHA Throughput for One-Relay Two-Hop Wireless Network Coding -- Exact Models for the k-Connected Minimum Energy Problem -- Performance Evaluation of Quality of Service in IEEE 802.11e Wireless LANs -- Cooperative Localization in GPS-Limited Urban Environments -- Tracking a Vehicle Moving in a Wireless Sensor Network -- Improved Topology Control Algorithms for Simple Mobile Networks -- Reliable Coverage Area Based Link Expiration Time (LET) Routing Metric for Mobile Ad Hoc Networks -- Constructing Minimum Relay Connected Sensor Cover in Heterogeneous Wireless Sensor Networks -- Experimentation Made Easy -- Enhancing Learning Using Modular Wireless Sensor Networking (WSN) Hands-On Experiments -- Sensor Network in the Wireless UHF Band -- VoIP Implementation and Experiments on a Mobile Wireless AdHoc Network -- Relay Implementation in WiMAX System Level Simulator -- MeshMAC: Enabling Mesh Networking over IEEE 802.15.4 through Distributed Beacon Scheduling -- Compressing MAC Headers on Shared Wireless Media -- An RTS Based Data Channel Reservations and Access Scheme in Multi-Channel Systems -- Building Intrusion Detection with a Wireless Sensor Network -- Passive and Active Analysis in DSR-Based Ad Hoc Networks -- An E-Hospital Security Architecture -- Cooperative Certificate Revocation List Distribution Methods in VANETs -- Distributed Channel Selection for Ad-Hoc Networks in the Presence of Jamming Sources -- Joint Random Access and Power Control Game in Ad Hoc Networks with Noncooperative Users -- Graph Marginalization for Rapid Assignment in Wide-Area Surveillance -- Error Correction with the Implicit Encoding Capability of Random Network Coding -- An End-to-End Loss Discrimination Scheme for Multimedia Transmission over Wireless IP Networks -- International Workshop on Advanced Sensor Integration Technology -- Architecture for WSN Nodes Integration in Context Aware Systems Using Semantic Messages -- Performance Analysis of ZigBee Technology for Wireless Body Area Sensor Networks -- Analytical Models of Cross-Layer Protocol Optimization in Real-Time Wireless Sensor Ad Hoc Networks -- Programmable Re-tasking of Wireless Sensor Networks Using WISEMAN -- Oxybuoy: Constructing a Real-Time Inexpensive Hypoxia Monitoring Platform -- An Energy-Efficient, Application-Oriented Control Algorithm for MAC Protocols in WSN -- An Integrated RFID and Sensor System for Emergency Handling in Underground Coal Mines Environments -- An Area-Based Overlay Architecture for Scalable Integration of Sensor Networks -- International Workshop on Cross-Layer Design in Wireless Mobile Ad Hoc Networks -- Outage Probability for ARQ Decode-and-Forward Relaying under Packet-Rate Fading -- Distributed Spectrum Sharing for Video Streaming in Cognitive Radio Ad Hoc Networks -- The Cognitive Radio Channel: From Spectrum Sensing to Message Cribbing -- AM-AOMDV: Adaptive Multi-metric Ad-Hoc On-Demand Multipath Distance Vector Routing -- A Low-Latency TDMA Scheduler for Multi-hop Cluster Based MANETs with Directional Antennas.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Computer system performance; Software engineering; Data protection; Data structures (Computer science).; Computer Science; Computer Communication Networks; Computer Systems Organization and Communication Networks; Software Engineering/Programming and Operating Systems; System Performance and Evaluation; Data Structures, Cryptology and Information Theory; Systems and Data Security